Best friends - Martin, Ann M., 1955- (New York : Scholastic, 2008)
As Flora and Ruby near the first anniversary of their arrival in Camden Falls, Flora has to deal with rivalry between Annnika and Olivia, her old and new best friends as the town celebrates it's 350th birthday.
"This edition is available for distribution only through the school market"--Cover verso.
Includes an interview with the author.
Keywords: Best friends -- Juvenile fiction; Sisters -- Juvenile fiction; Orphans -- Juvenile fiction; Best friends -- Fiction; Friendship -- Fiction; Sisters -- Fiction; Orphans -- Fiction